2014
DOI: 10.1016/j.rbmo.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of PTGS2-generated PGE2 during gonadotrophin-induced bovine oocyte maturation and cumulus cell expansion

Abstract: (AA Fouladi-Nashta).Waleed Fawzy A Marei is a veterinarian and graduated from Cairo University, Egypt in 2001. He started his academic career in theriogenology in 2002 and obtained his MSc degree in 2005. He joined the reproduction research group at the Royal Veterinary College, London, UK and investigated the effects of fatty acids on oocyte quality and early embryo development for his PhD, awarded in 2010. He then pursued post-doctoral research in the same group, working on early embryo development and impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 58 publications
4
34
1
1
Order By: Relevance
“…Similar result was reported that LA significantly inhibits GV breakdown (35% in LA vs. 81% in control) in cumulusfree oocytes (Homa et al, 1992). (Marei et al, 2014). In mammals, LA can be transformed to DGLA and AA, and ALA can be transformed to EPA, and specifically, DGLA is a precursor for 1-series PG synthesis (PGF 1 or PGE 1 ), AA is a precursor for 2-series PG synthesis (PGF 2 or PGE 2 ), and EPA is a precursor for 3-series PG synthesis (PGF 3 or PGE 3 ) (Wathes et al, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…Similar result was reported that LA significantly inhibits GV breakdown (35% in LA vs. 81% in control) in cumulusfree oocytes (Homa et al, 1992). (Marei et al, 2014). In mammals, LA can be transformed to DGLA and AA, and ALA can be transformed to EPA, and specifically, DGLA is a precursor for 1-series PG synthesis (PGF 1 or PGE 1 ), AA is a precursor for 2-series PG synthesis (PGF 2 or PGE 2 ), and EPA is a precursor for 3-series PG synthesis (PGF 3 or PGE 3 ) (Wathes et al, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…The results showed that 5 ÎźM D4476 significant inhibited cumulus cell apoptosis, and promoted cumulus cell proliferation and expansion. Furthermore, expansion genes PTGS‐2, PTX‐3 and TGS‐6 were marker genes for oocyte maturation quality (Maina et al, ; Marei, Abayasekara, Wathes, & Fouladi‐Nashta, ; Salustri et al, ; Wisniewski & Vilček, ). Consequently, we speculated that D4476 improved developmental competence of oocytes by promoting proliferation and expansion of CCs.…”
Section: Discussionmentioning
confidence: 99%
“…Expression and enzyme activity of aromatase CYP19A1, responsible for the conversion of androgens into oestrogens, for example, are regulated by FSH as demonstrated in bovine granulosa cells (Gutierrez, Campbell, & Webb, ). Genes regulating cumulus expansion by prostaglandin synthesis such as prostaglandin‐endoperoxide synthase 2 (PTGS2 or COX2), and PTGES, depend also on gonadotropin stimulation (Marei, Abayasekara, Wathes, & Fouladi‐Nashta, ).…”
Section: Discussionmentioning
confidence: 99%